The first national pediatric immune thrombocytopenia registry in Iran: research protocol and preliminary study results - Sharareh Kamfar; Sabahat Haghi; Vahide Zeinali; Parastoo Molaei Tavana; Reza Arjmand; Fatemeh Malek (BMC, 2024)
Abstract Background Disease registries are comprehensive databases that record detailed information on patients diagnosed with specific conditions, providing valuable insights into their diagnosis, treatment, and outcomes. This study aims to describe the pilot phase of the national pediatric Immune Thrombocytopenia(ITP) registry (NPITP) in Iran, serving as the inaugural interpretive report. Methods This patient-centered software system was implemented as a national program across multiple pediatric centers in Iran. Several focus groups were conducted to establish a minimum data set (MDS) comprising six main classes, 14 sub-classes, and 187 data elements. Following expert consensus on the final data set, a web-based software tool was developed by the dedicated IT team, accessible online and offline via https://disreg.sbmu.ac.ir/q/ITP.html . The registry included children aged between two months and 18 years with a platelet count below 100 × 109/L, based on predefined inclusion criteria. Results Within a four-month period, a total of 60 ITP patients were registered, including 41 (68.3%) newly diagnosed cases, 68 (13.6%) persistent cases, and 14 (23.3%) with chronic ITP. The mean age of the registered patients was 55.93 ± 9.72 months. The most frequently observed bleeding symptoms were petechiae (68.3%), purpura (51.6%), and ecchymosis (13.3%). Among the newly diagnosed patients, 20 (33.3%) received intravenous immunoglobulin (IVIG), 17 (28.3%) were treated with prednisolone, and 17 (28.3%) received combined IVIG and steroid therapy. Of all patients, 40 (66.7%) demonstrated a complete response to treatment, while 16 (26.7%) exhibited a partial response. Four patients (6.7%) remained unresponsive to therapy. Treatment-related complications, such as Cushing's syndrome, edema, weight gain, hirsutism, and mood disorders, were reported in 10 patients (16.6%). However, the majority of patients (81.7%) did not experience therapy-related complications. Conclusion The pilot phase of the NPITP registry successfully implemented a web-based software tool for data collection, aiming to enhance the quality of care, facilitate clinical research, and support health service planning in the future.